Social-ecological correlates of fundamental movement skills in young children - Nan Zeng; Susan L. Johnson; Richard E. Boles; Laura L. Bellows (Elsevier, 2019)
Purpose: To identify the social-ecological correlates associated with fundamental movement skills at the child, family, and environment levels in young children. Methods: Preschool children from 4 Colorado Head Start/preschool centers were recruited from 2010 to 2012. Two hundred twenty-eight children (128 girls; age = 56.08 ± 4.09 months; body mass index (BMI) z-score = 0.53 ± 1.12 (mean ± SD); 42.1% Hispanic/Latino) and 159 families were included in the final analysis. Children's perceived competence and fundamental movement skills were assessed via the Pictorial Scale of Perceived Competence and Social Acceptance and the Bruininks-Oseretsky Test of Motor Proficiency, 2nd edition. Data on the number of children in the family, parent age, BMI, education, employment status, family income, perception of child coordination, and home physical activity environment were collected via a questionnaire. Linear regressions adjusted for child BMI, age, sex, and school site were performed at each level. Results: Child perceived cognitive competence was positively associated with locomotor skills (p = 0.04; adjusted R2 = 0.035) and object-control skills (p = 0.003; adjusted R2 = 0.083) at the child level. Parent education, BMI, and perception of child coordination were positively associated with locomotor skills and explained 8.8% of variance, but only parent education was significant (p = 0.04) at the family level. In addition, physical environment was positively associated with locomotor skills (p = 0.02) and explained 5.5% of variance at the environment level. Conclusion: Social-ecological correlates associated with young children's fundamental movement skills are multidimensional and differ according to skill category at the child, family, and environment levels. Keywords: Activity environment, Fundamental movement skills, Parent education, Perceived cognitive competence, Preschool children